2D-3D Phase Transition in Ultra-thin H2TPP Films Induced by Deposition of Iron Atoms. (2015) - Picone, A.; Bussetti, G.; Riva, M.; Brambilla, A.; Finazzi, M.; Ciccacci, F.; Duò, L.
Abstract: The sublimation of free base porphyrin (namely H2 TPP) in ultra-high vacuum on graphite results in a three dimensional clusters growth. On the other hand, a two dimensional layer of free base porphyrin can be obtained by a post growth chemical treatment of the sample, based on hydrochloric vapor exposure. In this work, the morphological modifications induced by the sublimation of Fe atoms on the porphyrins two dimensional film are investigated by means of scanning tunneling microscopy. We provide the evidence that the porphyrins film undergoes to a recrystallization process, induced by the interaction with Fe atoms. A new treatment with hydrochloric vapor removes the three dimensional porphyrins clusters again.